Astragaloside IV Protects 6-Hydroxydopamine-Induced SH-SY5Y Cell Model of Parkinson’s Disease via Activating the JAK2/STAT3 Pathway - Xu, ZhengHu; Yang, Dongfeng; Huang, Xiaojing; Huang, Huai (Frontiers in Neuroscience, 2021)
Objectives: Astragaloside IV (AS-IV), the main active component of Astragalus membranaceus, bears anti-inflammatory, antioxidant and neuroprotective activity. Parkinson's disease (PD) is a common neurodegenerative disease. This study explored the protective effect of AS-IV on the cell model of PD. Methods: SH-SY5Y cells were incubated with different concentrations (10, 50, 100, 150 and 200 μM) of 6-hydroxydopamine (6-OHDA) for 0, 3, 6, 12, 24 and 48 h to establish the PD cell model. Different concentrations (0, 25, 50, 100, 150 and 200 μM) of AS-IV or 15 mM JAK2/STAT3 pathway inhibitor SC99 was added for intervention 2 h before 6-OHDA treatment. The viability and morphological damage of 6-OHDA-treated SH-SY5Y cells were measured using MTT assay and Hoechst 33258 staining. The expression of microtubule associated protein 2 (MAP2) was detected by immunofluorescence staining. The levels of inflammation and oxidative stress were measured using ELISA. Apoptosis of 6-OHDA-treated SH-SY5Y cells was detected using flow cytometry, and phosphorylation level of JAK2 and STAT3 were detected using Western blot analysis. Results: The survival rate of SH-SY5Y cells treated with 100 μM 6-OHDA for 24 h was about 50%. AS-IV (25-100 μM) significantly improved the viability (all p < 0.01), increased MAP2 expression, and repaired the morphological damage induced by 6-OHDA. AS-IV inhibited IL-1β, IL-6 and TNF-α level (all p < 0.05), reduced MDA and ROS content and increased SOD concentration, thereby reducing inflammation and oxidative stress (all p < 0.01) in 6-OHDA-treated SH-SY5Y cells. Moreover, AS-IV decreased apoptosis rate and Bax/Bcl-2 ratio induced by 6-OHDA (all p < 0.05). Mechanically, AS-IV significantly increased the phosphorylation of JAK2 and STAT3 (p < 0.01); the addition of SC99 decreased the cell viability, increased the apoptosis rate, enhanced the levels of inflammatory factors and oxidative stress. Conclusion: AS-IV enhanced the cell viability, and inhibited apoptosis, inflammation and oxidative stress of 6-OHDA-treated SH-SY5Y cells via activating the JAK2/STAT3 signaling pathway. This study may confer novel insights for the management of PD.